Supplementation of Zinc Palm Oil Soap Improves Feed Fermentability and Unsaturated Fatty Acid Profile in Rumen Liquid - Muktiani, A.; Widiyanto, W.; Pandupuspitasari, N. S. (Tropical Animal Science Journal, 2024)
This study aimed to evaluate the effects of energy and organic zinc supplements, specifically zinc palm oil soap (ZPOS), on digestibility and unsaturated fatty acid profiles in vitro. The study used a completely randomized design with 4 treatments and 5 replications. The treatments were: T0= basal diet without supplementation, T1= basal diet + 5% palm oil (PO), T2= basal diet + 5% partial ZPOS (3.75% ZPOS + 1.25% PO), and T3= basal diet + 5% ZPOS. The inoculum source was rumen liquid from three fistulated female dairy goats and was homogenized. The goats were fed ration consisting of corn straw, soybean hulls, and concentrate containing total digestible nutrients (TDN) 63%, crude protein (CP) 14%, and neutral detergent fiber (NDF) 35%. Results showed that both 5% partial ZPOS and 5% ZPOS supplementation (T2 and T3) resulted in the increase of total volatile fatty acids (VFA), acetate, propionate, butyrate, unsaturated fatty acids (USFA) and a decrease in the ratio of acetate/propionate (A/P) compared to the control and supplementation of 5% PO (p<0.05). Supplementation of 5% partial ZPOS (T2) is better than 5% ZPOS because increased the digestibility of ether extract (EE), crude fiber (CF), NDF, and acids detergent fiber (ADF) (p<0.05) and decreased of methane compared to the control (p<0.05). In conclusion, adding 5% partial ZPOS (3.5% ZPOS and 1.5% PO) increases fiber digestibility, VFA, LCFA, and USFA concentration, and decreases methane production in the rumen liquid.